Identification of VAT1-associated immune infiltration and its prognostic significance in skin cutaneous melanoma - Zide HONG; Bin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective To explore the immune infiltration and prognostic significance of vesicle amine transport protein-1(VAT1) in skin cutaneous melanoma (SKCM). Methods Gene expression profiling interactive analysis (GEPIA) was used to analyze expression levels of VAT1 mRNA in SKCM, and the human protein atlas (HPA) was used to measure expression levels of VAT1 protein. The survival module of GEPIA was used to assess the effect of VAT1 on the survival of SKCM patients, and the results were verified with GSE98394 dataset downloaded from TCGA. Univariate Cox proportional-hazards model was used to assess the relationship between VAT1 and survival rate. In addition, the tumor immune evaluation resource (TIMER) was used to study the relationship between the level of immune invasion and the expression levels of VAT1, as well as the relationship with cumulative survival rate of SKCM. CIBERSORT was used to study the correlation between VAT1 and tumor immune invasion. Results Expression levels of both VAT1 mRNA and protein were higher in SKCM patients than those in normal subjects. Survival curve and univariate Cox model showed that the upregulation of VAT1 was a poor prognostic factor for SKCM. The expression levels of VAT1 were negatively correlated with the infiltration of CD8+ T cells, macrophages, neutrophils and dendritic cells in SKCM. In addition, tissues with high expression levels of VAT1 differed significantly from those with low expression levels of VAT1 in the proportion of immune cells such as resting memory CD4+ T cells, activated memory CD4+ T cells, M1 macrophages, resting mast cells, regulatory T cells, activated NK cells and plasma cells. Conclusion VAT1 is a potential, prognostic biomarker of SKCM, which is related to immune infiltrations.